(untitled) (Communication & Society, 2021)
Research about the use of Artificial Intelligence applied to journalism has increased over the years. The studies conducted in this field between January 2008 and December 2019 were analysed to understand the contexts in which they have been developed and the challenges detected. The method used consisted of a systematic review of the scientific literature (SLR) of 209 scientific documents published in the Web of Science and Scopus databases. The validation required the inclusion and exclusion criteria, database identification, search engines and evaluation and description of results. The findings indicate that the largest number of publications related to this topic are concentrated in the United States and that the rise of scientific production on Artificial Intelligence in journalism takes place in 2015, when the remarkable growth of these publications begins, until reaching 61 in 2019. It is concluded that research is mainly published in scientific journals, which include works that handle a broad variety of topics, such as information production, data journalism, big data, application in social networks or information checking. In relation to authorship, the trend is the presence of a single signer.